2021
DOI: 10.1186/s13287-021-02412-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal induction of Lhx8 by optogenetic control system for efficient bone regeneration

Abstract: Background The spatiotemporal regulation of essential genes is crucial for controlling the growth and differentiation of cells in a precise manner during regeneration. Recently, optogenetics was considered as a potent technology for sophisticated regulation of target genes, which might be a promising tool for regenerative medicine. In this study, we used an optogenetic control system to precisely regulate the expression of Lhx8 to promote efficient bone regeneration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In terms of understanding and curing developmental and growth-related pathologies, great strides have been made in organoid engineering, tissue regeneration, etc. For example, Huang et al optogenetically activated the LIM Homeobox 8 (Lhx8) target gene to demonstrate the vital role of the gene in controlling complementary proliferation and osteogenic differentiation expressed in bone development [155][156][157]. As an optogenetic tool, FKF1 (flavinbinding, kelch repeat, f-box 1) receptor with a LOV domain temporally induced Lhx8 expression activatable with blue light.…”
Section: Conclusion and Translation Into New Applicationsmentioning
confidence: 99%
“…In terms of understanding and curing developmental and growth-related pathologies, great strides have been made in organoid engineering, tissue regeneration, etc. For example, Huang et al optogenetically activated the LIM Homeobox 8 (Lhx8) target gene to demonstrate the vital role of the gene in controlling complementary proliferation and osteogenic differentiation expressed in bone development [155][156][157]. As an optogenetic tool, FKF1 (flavinbinding, kelch repeat, f-box 1) receptor with a LOV domain temporally induced Lhx8 expression activatable with blue light.…”
Section: Conclusion and Translation Into New Applicationsmentioning
confidence: 99%
“…In recent years, MSC therapy has shown great potential to promote bone healing [ 109 ]. It has been shown that MSCs can directly differentiate into osteoblasts and osteocytes, secrete various bioactive substances and acquire similar functions to bone tissue [ 52 ]. For example, Sayanti Datta et al.…”
Section: Applications Of the Hydrogelsmentioning
confidence: 99%
“…Multiple PAP pairs undergo heterodimerization, such as blue‐light‐sensitive pairs CRY2/CIB (Kennedy et al, 2010), iLID (Guntas et al, 2015), TULIP (Strickland et al, 2012), Magnets (Kawano et al, 2015; Figure 1a). These optogenetic systems have been successfully used to control the activities of many proteins, including RhoGEFs and Rho GTPases activity for cytoskeleton reorganization (Deneke et al, 2019; Eritano et al, 2020; Krueger, Tardivo, Nguyen, & De Renzis, 2018), recombinase and Cas9 activity for genetic modification (Li et al, 2020; Nihongaki, Otabe, Ueda, & Sato, 2019), transcription factor activation, and gene expression (D. Huang et al, 2021; W. Wang et al, 2019), signaling effectors for signaling cascade activity modulation (Johnson, Djabrayan, Shvartsman, & Toettcher, 2020; Johnson et al, 2017; Johnson & Toettcher, 2019; Krishnamurthy et al, 2020; McFann, Dutta, Toettcher, & Shvartsman, 2021; Shao et al, 2017; Q. Wang et al, 2020), Rab11 activity for membrane trafficking regulation (Rathbun et al, 2020).…”
Section: Mechanisms Of Action For Opsin‐free Optogenetic Toolboxmentioning
confidence: 99%